Tindakan Komunikatif di Ruang Publik: Menilai Demokrasi Deliberatif Habermasian dalam Tata Kelola Digital - Oman Rohman Rakinda; Nisa Wening Asih Sutrisno; Rahmat Salam; Andriansyah Andriansyah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Digital governance is often expected to expand public participation, strengthen transparency, and foster deliberative democracy by enabling dialogic interaction between the state and citizens. Yet, whether digital government platforms can facilitate communicative action and equal deliberation remains contested, given risks of fragmentation, algorithmic influence, and unequal access. This study critically assesses the extent to which Habermasian deliberative democracy is realized in contemporary digital governance practices, examining whether government platforms function as arenas for rational deliberation or reproduce new forms of exclusion and social isolation. Using a qualitative approach based on critical literature review and conceptual analysis of policies, platform designs, and online participation practices, the study finds that while digital platforms open channels for two-way communication, participation is largely procedural, elitist, and fragmented. Digital spaces frequently operate as sites of symbolic expression rather than substantive deliberation, shaped by technocratic rationality and structural power. The study argues that strengthening deliberative democracy requires participatory platform architecture, transparent policy feedback, and efforts to reduce algorithmic domination and digital inequality.